Renoprotective Effect Of Sambiloto (Andrographis Paniculata) Leaf Extract On Lipopolysaccharide – Induced Septic Rats - Adhika Bastian Bagas Prananta; Nyoman Suci Widyastiti; Ariosta Ariosta; Dwi Retnoningrum; Rezya Salsabela; Vega Karlowee; Neni Susilaningsih (Journal of Biomedicine and Translational Research, 2023)
Background: Associated with sepsis is the illness known as acute kidney injury (AKI). AKI may be mediated by uric acid, and blood creatinine levels can be utilized to diagnose the condition to measure kidney function. Sambiloto (Andrographis paniculata) is a traditional medicine that has flavonoid compounds that can reduce creatinine levels and Xanthine Oxidase Inhibitors which can reduce uric acid levels.Objective: Septic model rats generated by lipopolysaccharide were used to test the effects of sambiloto (Andrographis paniculata) leaf extract on serum creatinine and uric acid levels (LPS).Methods: This study was experimental employing 25 rats split into 5 groups as the post-test alone control group: healthy control with standard feed (HC), negative control with LPS injection(NC), Treatment (T)1 (A.Paniculata 200 mg/kgBW+LPS), T2(A.paniculata 400 mg/kgBW+LPS), and T3(A.paniculata 500mg/kgBW+ LPS). A.paniculata leaf extract was given via oral gavage on day 8-21. Intraperitoneal injection of LPS 5 mg/kgBW was given on day 22. On the 25th day, the blood serum was analyzed for creatinine levels using Jaffe method and uric acid was analyzed using the enzymatic photometric method. One-way analysis of variance (Kruskal-Wallis) and the Kruskal-Wallis test were used to evaluate the data.Results: The mean creatinine levels of HC,NC,T1,T2,T3 were 0.7±0.01;3.5±0.04;2.9±0.03;1.9±0.05; 1.3 ±0.04 mg/dl respectively. The mean uric acid levels of HC.NC.T1.T2.T3 were 1.7±0.05;8.2±0.11; 4.5±0.03;4.0±0.12;3.0±0.19 mg/dl respectively. There were significant differences (p<0.05) in creatinine levels in groups T2(p=0.031) and T3(p=0.001) to NC group and serum uric acid levels in groups T1(p<0.001), T2(p<0.001), and T3(p<0.001) to NC group which creatinine and uric acid levels were lower than NC group.Conclusion: Andrographis paniculata leaf extract has renoprotective effect against AKI in LPS-induced septic ratsKeywords: Andrographis paniculata, creatinine, uric acid, lipopolysaccharide, AKI, sepsis